PKM HORISON HARAPAN BUMDESA “JATIDIRI” MELALUI UNIT USAHA BERBASIS KERAJINAN DAN SENI BUDAYA DI DESA JATIGUWI SUMBERPUCUNG MALANG - Dhanny Septimawan Sutopo; Arief B. Nugroho; Anif Fatma Chawa (LPPM Universitas Bina Bangsa, 2023)
Jatiguwi Village is a rural area located in Sumberpucung District, Malang Regency, East Java Province and is located about 35 km to the southwest of Malang City. The opportunity for economic development in Jatiguwi Village has begun to be promoted through Village-Owned Enterprises (BUM Desa). In this village, BUMDesa has been formed since 2016 under the name of